2015
DOI: 10.1016/j.ihj.2015.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac syndrome X: Clinical characteristics revisited

Abstract: Cardiac syndrome X constitutes a significant subset of patients undergoing coronary angiography. It is essential to identify and treat them specifically for microvascular angina. Many of them have atherosclerotic risk factors but their presentation is different from those with obstructive coronaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…MVA, otherwise called cardiac syndrome X, is a diagnosis of exclusion that has been attributed to coronary microvascular dysfunction (CMD) by many studies. [4][5][6][7][8][9][10][11][12] Contributing factors include endothelial dysfunction, inflammation, atherosclerosis, sluggish coronary blood flow, and increased sympathetic output. It has been found that patients with endothelial dysfunction have reduced levels of endothelium-derived nitric oxide (NO) with elevated levels of endothelin-1 (ET-1), resulting in impaired local vasodilatation at capillary beds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MVA, otherwise called cardiac syndrome X, is a diagnosis of exclusion that has been attributed to coronary microvascular dysfunction (CMD) by many studies. [4][5][6][7][8][9][10][11][12] Contributing factors include endothelial dysfunction, inflammation, atherosclerosis, sluggish coronary blood flow, and increased sympathetic output. It has been found that patients with endothelial dysfunction have reduced levels of endothelium-derived nitric oxide (NO) with elevated levels of endothelin-1 (ET-1), resulting in impaired local vasodilatation at capillary beds.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that patients with endothelial dysfunction have reduced levels of endothelium-derived nitric oxide (NO) with elevated levels of endothelin-1 (ET-1), resulting in impaired local vasodilatation at capillary beds. 5, 11, 13 The depletion of local NO also favors platelet aggregation and the expression of E-selectin and vascular cell adhesion molecule-1 (VCAM-1), 9, 11, 13 which are both vital inflammatory mediators. Majidinia et al found that MVA patients had elevated levels of ET-1, VCAM-1, and E-selectin at rest compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With these patients the coronary angiography can appear normal (18). This is usually diagnosed based on chest pain typical for angina, exercise-induced significant ST-segment depression and normal coronary angiograms (19). Syndrome X is diagnosed based on chest pain, exercise-induced ST-segment depression and the absence of either significant epicardial coronary stenosis or vasospasm (20).…”
Section: Methodsmentioning
confidence: 99%
“…Согласно Рекомендациям ESC (2019), БКА -это патологический процесс, характеризующийся формированием атеросклеротических бляшек в эпикардиальных артериях, приводящих или не приводящих к их обструкции [1]. В других работах [3][4][5][6][7][8][9] отмечается, что наличие клинических симптомов, типичных для ИБС, и выявление признаков ишемии миокарда с помощью инструментальных методов исследования не всегда сопровождается атеросклеротическим поражением крупных коронарных артерий.…”
Section: обзоры §unclassified